Carriage of Neisseria meningitidis and Neisseria lactamica in a school population during an epidemic period in Spain. - Saez-Nieto, J. A. (Cambridge University Press, 1985)
A study was made of the incidence of Neisseria meningitidis and N. lactamica in a school population; 2470 children aged between 5 and 7 years were studied from four schools in Alcala de Henares (Madrid). Nasopharyngeal swabs were taken in June, November and March, between 1979 and 1983. In all the surveys except one, the proportion of carriers of N. lactamica was higher than that of N. meningitidis, reaching a ratio of about 2:1 in the complete study. The predominant serogroup of meningococcus found was B (41%), with nongroupable strains reaching 43%. A study of serotypes within group B showed a predominance of nontypable strains (48.5%), while those strains considered to be most virulent (types 2 and 1, 8, 15) reached 40%. Eighteen per cent of N. lactamica strains were observed to agglutinate with antimeningococcal sera whilst the remainder of the strains were rough. When these strains were studied with the antiserum-agar technique, using antimeningococcal sera, a high percentage of strains cross-reacted with the meningococci. The susceptibility of strains to sulphadiazine, penicillin, ampicillin, chloramphenicol, rifampicin and spiramycin was determined. Finally an analysis was made of the effect that an elevated colonization rate of N. lactamica might have on colonization by meningococci. The necessity of using fine epidemiological markers in tracing virulent strains in a population at risk is stressed. Selective prophylactic measures are also necessary.